Trademarks as Sources of Market Power: Drugs, Beers and Product Differentiation - Morris, P. Sean (Journal of Law and Commerce, 2017)
This Article defines the notion of market power and how in conjunction with trademark rights give rise to elements that are deemed anticompetitive in a free market society. This Article uses legal arguments to consider how important developments in antitrust economics, particularly product differentiation and monopolistic competition, have contributed to the notion that trademarks are a source of market power. The Article uses a number of cases in the field of trademarks to underscore the key points that trademarks are a source of market power. These case developments contribute to the monopolistic tendencies of trademarks and describe how such tendencies are associated with the theory on market power and product differentiation. Empirically, the Article examines beer products from a single large corporation and the various trademarks/brands to determine whether such brands are a source of market power, effectively giving that manufacturer a monopoly on the beer market. A discussion of product hopping in pharmaceuticals is used to supplement the theories and evidence from the beer market. The Article also develops a theory of branded monopoly and suggests that, as a result of single ownership of trademarks and brands that are abundant from a single owner trademark’s market power, questions relating to antitrust foreclosure are often raised, despite the fact that market power is not anticompetitive per se. If it is recognized that trademarks are a source of market power, and hence, a core concern for antitrust law and policy, then the legal foundations of the current trademark system would need a radical redesign. If, on the other hand, it is recognized that trademarks are a source of market power, but do not conflict with antitrust law, and antitrust enforcers are to ignore conducts such as market foreclosure and other barriers to entry as a result of excessive trademarks and brands, then both antitrust and trademark law can continue to co-exist in the current system.